2014
DOI: 10.1177/0142723714534220
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of preschool children’s discussions with parents during picture book and chapter book reading

Abstract: Discussions that occur during book reading between parents and preschool children relate to children’s language development, especially discussions during picture books that include extended discourse, a form of abstract language. While a recent report shows increased chapter book reading among families with preschool children, it is unknown whether chapter books also facilitate these types of conversations. Further, the substantial variation in preschoolers’ language ability raises the question of whether cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
2
21
0
2
Order By: Relevance
“…Similarly, Leech and Rowe (2014) compared 5-year-old children’s ( N = 33) discussions with their parents during picture book and chapter book reading (chapter books tell the story primarily through the text, although they tend to be profusely illustrated). There was variation in the amount and type of discussion between contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Leech and Rowe (2014) compared 5-year-old children’s ( N = 33) discussions with their parents during picture book and chapter book reading (chapter books tell the story primarily through the text, although they tend to be profusely illustrated). There was variation in the amount and type of discussion between contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Second, studies examining the extra-textual talk produced by caregivers when sharing books with young children (see Fletcher & Reese, 2005, for a comprehensive review; also Leech & Rowe, 2014) demonstrate its qualitative and quantitative benefits when compared to everyday CDS (e.g., Hayes & Ahrens, 1988; Snow, Arlman-Rupp, Hassing, Jobse, Joosten, & Vorster, 1976). For example, Hoff-Ginsberg (1991) analysed mothers’ speech across four contexts (mealtimes, dressing, toy play, and book reading) and found that the mothers’ rate of speech, MLU, and lexical diversity was highest during the book reading activity.…”
mentioning
confidence: 99%
“…When new forms of interaction are combined with content, they can induce pleasure in preschool children. Furthermore, Leech and Rowe (2014) found that picture books can be easily understood by preschool children and can lead to subsequent discussions about this content with their parents, meaning that they also help children’s language development. Preschoolers can easily interact with books according to their intentions, which increases their sense of participation and enhances positive emotions.…”
Section: Discussionmentioning
confidence: 99%
“…For preschool children, the most attractive interactive book form was folding interaction, while the overall sensory interaction was higher than behavioral interaction. Preschool children are curious, they read pictures rather than words, and pictures helped them understand the story ( Leech and Rowe, 2014 ; Li and Zhu, 2017 ), thus interactions that changed the picture into a different story attracted them the most. Behavioral interaction is an important factor in the design of books and could affect how they display illustrations and words.…”
Section: Discussionmentioning
confidence: 99%